2020
DOI: 10.3389/fphar.2020.01063
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of HIF-1α in Human Retinal Endothelial Cells Modulates Expression of miRNAs and Proangiogenic Growth Factors

Abstract: Retinal hypoxia is one of the causative factors of diabetic retinopathy and is also one of the triggers of VEGF release. We hypothesized that specific dysregulated miRNAs in diabetic retinopathy could be linked to hypoxia-induced damage in human retinal endothelial cells (HRECs). We investigated in HRECs the effects of chemical (CoCl 2 ) hypoxia on the expression of HIF-1α, VEGF, PlGF, and of a focused set of miRNAs. We found that miR-20a-5p, miR-20b-5p, miR-27a-3p, miR-27b-3p, miR-206-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 72 publications
2
25
1
Order By: Relevance
“…Altogether, these experimental observations would suggest that in RPE cells exposed to HG stress induction of autophagy represents a cytoprotective response. Accordingly, treatment with fenofibrate, a peroxisome proliferator-activated receptor alpha (PPARα) agonist by preventing ER-stress and inducing autophagy, exhibited a protective effect in RPE cells exposed to hyperglycemia (25 mM, 18 days) and hypoxia (1% oxygen, for 6 h or 24 h), two components of the diabetic milieu (Miranda et al, 2012;Lazzara et al, 2020).…”
Section: Retinal Pigment Epithelial Cellsmentioning
confidence: 99%
“…Altogether, these experimental observations would suggest that in RPE cells exposed to HG stress induction of autophagy represents a cytoprotective response. Accordingly, treatment with fenofibrate, a peroxisome proliferator-activated receptor alpha (PPARα) agonist by preventing ER-stress and inducing autophagy, exhibited a protective effect in RPE cells exposed to hyperglycemia (25 mM, 18 days) and hypoxia (1% oxygen, for 6 h or 24 h), two components of the diabetic milieu (Miranda et al, 2012;Lazzara et al, 2020).…”
Section: Retinal Pigment Epithelial Cellsmentioning
confidence: 99%
“…Zhang et al [ 30 ] interfered HIF-1α with small molecular RNA in mice, and found that silencing of HIF-1α could reduce VEGF expression and inhibit angiogenesis. In chemical (CoCl 2 ) hypoxia-induced hRECs, the expression of HIF-1α and VEGF was increased and activation of HIF-1α could upregulate the expression of VEGF [ 31 ]. HG-induced increased expression of VEGF, leading to the induction of apoptosis of hRECs via binding to VEGFR2 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…EPO treatment can effectively protect the nervous system and optic nerve development of premature infants[ 42 , 43 ]. HIF-1α is stably expressed under hypoxia; it can regulate EPO and VEGF expression and promote RNV[ 44 , 45 ]. Inhibiting the VEGF/VEGFR2 and HIF-1α/VEGF signaling pathways can prevent angiogenesis[ 46 ].…”
Section: Discussionmentioning
confidence: 99%